2003
DOI: 10.1161/01.cir.0000087480.94275.97
|View full text |Cite
|
Sign up to set email alerts
|

From Vulnerable Plaque to Vulnerable Patient

Abstract: Abstract-Atherosclerotic cardiovascular disease results in Ͼ19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
811
3
19

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 2,187 publications
(849 citation statements)
references
References 103 publications
16
811
3
19
Order By: Relevance
“…Overnight polysomnography was performed at nationally accredited sleep centers, and final diagnosis with apnea-hypopnea index (AHI; measure of the severity of disease) was available in all patients included in this study. Obstructive sleep apnea was further classified as no OSA (AHI <10), mild OSA (AHI [10][11][12][13][14][15][16][17][18][19][20], and severe OSA (AHI> 20). The number of vessels involved was defined as 0 if there was no stenosis and 1 if any stenosis or plaque was present.…”
Section: Imaging Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Overnight polysomnography was performed at nationally accredited sleep centers, and final diagnosis with apnea-hypopnea index (AHI; measure of the severity of disease) was available in all patients included in this study. Obstructive sleep apnea was further classified as no OSA (AHI <10), mild OSA (AHI [10][11][12][13][14][15][16][17][18][19][20], and severe OSA (AHI> 20). The number of vessels involved was defined as 0 if there was no stenosis and 1 if any stenosis or plaque was present.…”
Section: Imaging Techniquementioning
confidence: 99%
“…13 -15 It is believed that the noncalcified plaques and mixed plaques are more prone to rupture and may play an important role in ACS. 16 The traditional noninvasive imaging techniques do not identify noncalcified plaques. Multidetector-row computed tomography (MDCT) recently has been demonstrated as a reliable noninvasive technique for detection and characterization of noncalcified atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%
“…The PROSPECT study16 of coronary atherosclerosis demonstrated that cardiac events were related to high atherosclerotic burden rather than the severity of coronary artery stenosis. It is now accepted that atherosclerotic burden in coronary arteries is more important than stenosis in predicting subsequent cardiovascular events17, 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…However, luminal narrowing measured by angiography usually underestimates the disease severity due to positive remodeling effect and lacking of compositional information, particularly intraplaque hemorrhage, which is critical for the assessment of plaque vulnerability 6. Transesophageal echocardiography (TEE) can be utilized for detecting atherosclerotic plaques in aortic arch but this imaging technique is invasive.…”
Section: Introductionmentioning
confidence: 99%